The Impact of Research and Development Spending on Firm Value Moderated by Product Diversification - Trianti, Khoiriyah; Rahmawati, Noni Mia; Aini, Yulis Nurul (Budapest International Research and Critics University, 2021)
The objective of the study is to examine research and development spending on firm value. In addition, the study aims to examine whether the product diversification may moderate the impact of research and development spending on firm value. This study uses secondary data drawn from the company's financial statements and processed using SPSS software aplication with hierarchical regression analysis of the data. The results of the study show research and development spending has a significant impact on firm value. Product diversification strengthens the impact of the research and development on the firm value. This study supports the theory resource-based view stating that the company is able to manage the resources and capabilities and the company in this case is the innovation it is able to have a competitive advantage among its competitors.